Topical antimicrobial agents for pediatric burns - Robert Cartotto (Burns & Trauma, 2017)
Abstract While topical antimicrobial agents are indicated for most if not all burn wounds, the choice of a topical agent must consider many factors such as the wound depth, anticipated time to healing, need for surgical intervention, and the known cytotoxicity of the agent. Especially relevant to the pediatric burn patient are the antimicrobial agent’s properties related to causing pain or irritation and the required frequency of application and dressings. This article will discuss the general principles surrounding the use of topical antimicrobials on burn wounds and will review the most common agents currently in use.